Most popular posts about suicide in blogs - Giachero Vedana, Kelly Graziani (2018)
This study reviewed suicide-related posts in blogs with Portuguese languages. Qualitative study conducted on Tumblr platform by searching the word “suicide”, the first 250 posts in Portuguese ranked as “most popular” were selected and submitted to Thematic Analysis. “Suffering and dissatisfaction with life” was the main theme. The painful relationships and suffering reinforced each other and both increased the expectation that death could be beneficial and eliminate problems and pain. The unsatisfactory relationships and social pressures of “being well” made it difficult to express suffering and seek help. Self-harm represented both delay and preparation for suicide. The “suicide prevention” was approached in the minority of the posts and it was related with criticisms, depreciation, and objection to suicide. Online and offline suicidal behavior prevention actions need to address the perspective on life and death, interpersonal relationships, self-mutilation, coping strategies, and solicitation / offer of help.